Community Vulnerability in Agrarian Conflict Areas: A Case Study in the Perum Perhutani KPH Indramayu Area - Churniawan Triatmojo; Soni Akhmad Nulhaqim; Wandi Adiansah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Agrarian conflict is one of the main factors contributing to the increasing vulnerability of communities, especially in rural areas that depend on natural resources. This study aims to analyze community vulnerability in the context of agrarian conflict in Loyang Village, Cikedung District, Indramayu Regency, which is within the working area of KPH Indramayu. This conflict involved the cultivating community, Perum Perhutani as the manager of the forest area, and PG Jatitujuh as the holder of the Right to Use Business (HGU), which was triggered by the change in the function of the forest area into sugarcane plantation land. This study uses a qualitative approach with data analysis from interviews and literature studies, and refers to the concept of vulnerability according to Moser which includes seven dimensions, namely labor, human capital, housing and infrastructure, household relations, social capital, natural capital, and financial capital. The results of the study show that the vulnerability of the people of Loyang Village is multidimensional and interrelated between dimensions of livelihood. High dependence on the agricultural sector, limited non-agricultural skills, and uncertainty of access to land are the main factors that strengthen structural vulnerability. In addition, inequality of access to financial resources and limited alternative economic opportunities further narrow people's adaptive capacity. On the other hand, household relations and social capital play a role as an adaptation mechanism, although they are limited and have not been able to overcome the root of the problem. Agrarian conflicts not only have an impact on economic aspects, but also affect social, ecological, and institutional stability. Thus, the vulnerability of the people of Loyang Village is the result of an interaction between structural, social, and ecological factors. Therefore, a comprehensive handling approach is needed through strengthening adaptive capacity, increasing access to resources, and improving agrarian policies that are more inclusive and equitable.